Implementation of Civic Values through Flag Ceremony for the Character Development of Love for the Country - Indah Zulaikha; Wakhudin Wakhudin (UM Purwokerto Press, 2023)
This study was done in light of how important it is for students to have a sense of pride in their country, which is starting to wane. Flag ceremonies are one approach to strengthen this aspect of the discipline.The purpose of this study is to ascertain how SD Negeri Karangasem 02 students' participation in the flag ceremony shaped their sense of patriotism. This study takes a qualitative approach and does descriptive research. According to the findings of a study on how the SD Negeri Karangasem 02 flag ceremony shaped people's attitudes about their country, it is still classified as very common or good in terms of these parameters.The building of a love of country through the flag ceremony, namely by constantly reminding, leading, and explaining the significance of the flag ceremony to pupils in order to instill in them a love of country.